PENGARUH PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY BERBANTUAN MEDIA MINI BOOK TERHADAP HASIL BELAJAR SISWA KELAS XI SMAN 11 LUWU - Yunus, Nur Muhajirah; Nurasia; Musdalifah (Jurnal Biogenerasi, 2025)
This research aims to determine: (1) the learning outcomes of class XI students at SMAN 11 Luwu before implementing the Two Stay Two Stray learning model assisted by Mini Book media; (2) learning outcomes of class XI students at SMAN 11 Luwu after implementing the Two Stay Two Stray learning model assisted by Mini Book media; (3) the effect of implementing the Two Stay Two Stray learning model assisted by Mini Book media on class XI students at SMAN 11 Luwu. The type of research used was quasi-experimental with a non-equivalent control group design. The population in this study were all class XI students of SMA Negeri 11 Luwu. The sample for this research was class XI MIPA3 with 34 students as the experimental class and class XI MIPA4 with 34 students as the control class. Sampling used purposive sampling technique. The instruments in this research were learning outcomes tests and learning implementation observation sheets. Research data were analyzed using descriptive statistical analysis and inferential statistics. The research results show that: (1) student learning outcomes before implementing the Two Stay Two Stray learning model assisted by Mini Book media obtained an average score of 41.47 in the very low category; (2) student learning outcomes after implementing the Two Stay Two Stray learning model assisted by Mini Book media obtained an average score of 84.20 in the high category; (3) the t-test results obtain a sig value of 0.000 ˂ 0.05, which means that H0 is rejected and H1 is accepted. Based on this explanation, it can be concluded that there is an influence of the application of the Two Stay Two Stray learning model assisted by Mini Book media on the learning outcomes of class XI students at SMA Negeri 11 Luwu.